2023
DOI: 10.1021/jacs.3c04927
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear-Electronic Orbital Quantum Dynamics of Plasmon-Driven H2 Photodissociation

Abstract: Leveraging localized surface plasmon resonances of metal nanoparticles to trigger chemical reactions is a promising approach for heterogeneous catalysis. First-principles modeling of such processes is challenging due to the large number of electrons and electronic excited states as well as the significance of nuclear quantum effects when hydrogen is involved. Herein, the nonadiabatic nuclear-electronic quantum dynamics of plasmon-induced H 2 photodissociation near an Al 13 − cluster is simulated with real-time… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…The effects of doping on the plasmonic resonance characters of silver and gold nanochains have been studied using TDDFT, and previous work showed that the metal atom dopants can lead to additional electronic excitation modes in the absorption spectrum, which will then enhance the collective excitations. ,, Compared with the previous studies, our work will be more focused on how doping affects plasmon-enhanced N 2 dissociation. To study the nuclear motions in excited states, various types of nonadiabatic quantum dynamics have been applied to examine the photocatalyzed process such as small molecule activation/dissociation. In this work, we applied mean-field Ehrenfest dynamics to watch the evolution of N 2 when interacting with a doped plasmonic silver nanowire.…”
Section: Introductionmentioning
confidence: 99%
“…The effects of doping on the plasmonic resonance characters of silver and gold nanochains have been studied using TDDFT, and previous work showed that the metal atom dopants can lead to additional electronic excitation modes in the absorption spectrum, which will then enhance the collective excitations. ,, Compared with the previous studies, our work will be more focused on how doping affects plasmon-enhanced N 2 dissociation. To study the nuclear motions in excited states, various types of nonadiabatic quantum dynamics have been applied to examine the photocatalyzed process such as small molecule activation/dissociation. In this work, we applied mean-field Ehrenfest dynamics to watch the evolution of N 2 when interacting with a doped plasmonic silver nanowire.…”
Section: Introductionmentioning
confidence: 99%
“…Because the quantum protons and electrons are described on the same footing within the NEO framework, the corresponding nuclear quantum effects and non-Born–Oppenheimer effects are inherently included. The recently proposed constrained NEO (cNEO) approach, , whereby the protonic position expectation value is constrained to the proton basis function center position, has been shown to produce accurate molecular spectra including anharmonic effects. The NEO approach has been applied to study nuclear quantum effects in organic molecules and, more recently, to plasmon-induced H 2 dissociation by an Al 13 – cluster …”
mentioning
confidence: 99%
“…By evolving multicomponent wave functions, where more than one type of particle is treated quantum mechanically, real-time theory is capable of simulating additional interesting physical phenomena. In particular, combining the nuclear–electronic orbital (NEO) framework, which treats electrons and nuclei on equal footing, ,, with real-time theory enables the calculation of vibrational spectra , as well as the simulation of photoinduced proton transfer , and plasmon-induced dissociation reactions.…”
mentioning
confidence: 99%